Pengaruh Terapi Musik Instrumental Terhadap Tekanan Darah Pada Lansia Hipertensi - Nur Kholifah; Sutanta Sutanta (Universitas Muhammadiyah Surakarta, 2021)
Background : Hypertensian can occur anyone, both men and women at any age. The elderly are at high risk of developing age-related degenerative diseases such as hypertension, one way to lower blood pressure in hypertensive sufferers using music therapy instrumental . The Aim :To Find out the effect of music therapy instrumental on blood pressure in elderly of hypertension at Panti Wredha Budhi Dharma Umbulharjo Yogyakarta. Methods :This research uses the pra ekperiment with One Group Pretest-Postest. The study population amounted to 52 elderly people , there are 30 samples elderly people by sampling methods using purposive sampling method. The research the method of data analysis uses Wilcoxon. Results : After performing music therapy instrumental showed blood pressure there are 28 people down (normal) and 2 fixed (high). The results ofthe Wilcoxon test, Z count value of -6.174 with p value 0,000 α = 0,05. Conclusion :There is a effect of music therapy instrumental on blood pressure in elderly of hypertension at Panti Wredha Budhi Dharma Umbulharjo Yogyakarta.